2005
DOI: 10.1111/j.1468-1331.2004.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between APOE polymorphisms and mesial temporal lobe epilepsy with hippocampal sclerosis

Abstract: To evaluate the hypothetical link between apolipoprotein E (APOE) polymorphisms and mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) and whether presence of APOE epsilon4 allele shortens the latent period between febrile seizures and epilepsy. A further interest is whether presence of APOE epsilon4 allele has an impact on severity of the disease. Forty-seven patients with MTLE-HS were compared with 62 controls. APOE polymorphisms were determined from lymphocytes by standard methods. Eight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
3
18
1
1
Order By: Relevance
“…A few inherited syndromes for focal seizures have been reported [23,24], and an increasing number of susceptibility candidate genes have been brought forward for focal seizures during recent years [25]. Particularly, the apolipoprotein E (ApoE) was shown as a susceptibility candidate gene for temporal lobe epilepsy located on 19q13 by several studies [26,27]. To sum up, we assume that some of the susceptibility candidate genes associated with focal seizures may contribute to tumor-related seizures also in patients with…”
Section: Discussionmentioning
confidence: 94%
“…A few inherited syndromes for focal seizures have been reported [23,24], and an increasing number of susceptibility candidate genes have been brought forward for focal seizures during recent years [25]. Particularly, the apolipoprotein E (ApoE) was shown as a susceptibility candidate gene for temporal lobe epilepsy located on 19q13 by several studies [26,27]. To sum up, we assume that some of the susceptibility candidate genes associated with focal seizures may contribute to tumor-related seizures also in patients with…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that apolipoprotein E polymorphism is not associated with the development of major seizure disorders including temporal lobe epilepsy [23][24][25]. Moreover, the inheritance of the ApoE ε4 allele is associated with increased risk of late posttraumatic seizures [26] and with earlier onset of temporal lobe epilepsy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding epileptic seizures, it has been observed that ApoE polymorphism is not associated with the development of major seizure disorders including temporal lobe epilepsy [51][52][53]. Nevertheless, studies reported an earlier onset of chronic temporal lobe epilepsy [54] as well as increased risk of late posttraumatic seizures [55] in patients carrying the ApoE4 genotype.…”
Section: Genetic Variants and Their Risk For Withdrawal Seizuresmentioning
confidence: 94%